The Seventh Tun Abdul Razak Memorial Lecture 1996: Human Rights And Economic Development - Kirby AC CMG, The Hon Justice Michael (Journal of Malaysian and Comparative Law, 1995)
Lecture delivered by the Hon Justice Michael Kirby AC CMG on 15 July 1996.